PEMBERDAYAAN MASYARAKAT UNTUK MENINGKATKAN PENDAPATAN PER KAPITA DAN PELESTARIAN EKOSISTEM LAUT DI DESA BONDALEM KECAMATAN TEJAKULA KABUPATEN BULELENG - Paramita, L.; Suparthana, I.P.; Yudantini, N.M. (Buletin Udayana Mengabdi, 2017)
The village of Bondalem in Tejakula, Buleleng Regency – Bali, have marine natural resources in the form of coral reefs. However per-capita income of its population is still relatively low. This activity aims to increase the productivity of the population which will impact the increasing income and welfare through guidance and training in the production of fish brine. Beside that, the activity also aims in order to be able to maintain the sustainability of marine ecosystems through education about rescue coral reefs and how to catch fish in good and correct manner. The participants came from two group of SMES Mina Utama and Mina Sari that add up to 17 peoples and all fishermen in the village of Bondalem. After being given guidance and training, participants are able to produce fish brine and can be sold higher (50%) compared to the fish which sold in fresh form. The Fishermen in the village of Bondalem now can understand how important the conservation of coral reefs which exist in their village that will also have an impact on increasing the income and welfare of the community itself.